Social Media Foreign Policy: Examining the Political Use of Social Media by Ethnic Identity Groups in the United States. (May 2016) - Rubenzer, Trevor
Several scholars have noted intergenerational differences between members of diasporic communities in the United States as a potential source of weakening strength among identity-based interest groups. For example, changing attitudes amongst the children and grandchildren of Cuban exiles in the US have been cited as sources of some recent changes in American foreign policy toward Cuba. One way for existing elites within diasporic interest groups to reach out to new generations of potential activists is through the use of social media outlets such as Facebook and Twitter. Scholars, to this point, have largely ignored the use of social networking by ethnic identity interests in the US. This article examines the use of social media by ethnic identity interest groups as an important new tool in this regard. Specifically, it attempts for the first time to measure the level of involvement in social media advocacy in a systematic matter. Results indicate that the most powerful ethnic identity groups in the US are also the most likely to have an active social media presence. In addition, groups that are 'generationally challenged' do not appear to be using social media to address this issue.